2007
DOI: 10.1063/1.2643374
|View full text |Cite
|
Sign up to set email alerts
|

Leakage current analysis of diamond Schottky barrier diode

Abstract: The current-voltage characteristics of non-punch-through-type diamond Schottky barrier diodes ͑SBDs͒ are analyzed by using thermionic and thermionic-field emission ͑TFE͒ models. Diamond SBD with defects such as nonepitaxial crystallites ͑NCs͒ shows shunt path conductance both under forward and reverse bias conditions. However, SBD without NCs shows a low reverse leakage current density of less than 1 ϫ 10 −11 A/cm 2 , which is more than 12 orders of magnitude smaller than the forward current density. From the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 131 publications
(71 citation statements)
references
References 15 publications
(14 reference statements)
1
70
0
Order By: Relevance
“…The leakage current in blocking condition considerably larger than the current originated from thermionic emission. The avalanche current multiplication is not observed in the reverse I-V characteristics, and the leakage current is estimated as the tunneling phenomenon stemming from thermionic field emission, whose details are discussed further in references [7,8,9]. The result shows that the diode retains a sufficiently high blocking voltage for high temperatures, e.g., −160 V for 250 • C. Fig.…”
Section: Fig 2 Reverse Blocking Characteristicsmentioning
confidence: 73%
“…The leakage current in blocking condition considerably larger than the current originated from thermionic emission. The avalanche current multiplication is not observed in the reverse I-V characteristics, and the leakage current is estimated as the tunneling phenomenon stemming from thermionic field emission, whose details are discussed further in references [7,8,9]. The result shows that the diode retains a sufficiently high blocking voltage for high temperatures, e.g., −160 V for 250 • C. Fig.…”
Section: Fig 2 Reverse Blocking Characteristicsmentioning
confidence: 73%
“…With this structure, high performance SBD can be made as indicated above. The mechanism of the reverse leakage current has been analysed and found that it is in good agreement with the tunnelling model described by thermionic-field emission (TFE) rather than the conventionally used barrier-lowering model [8]. One of the techniques for Schottky contact formation is surface oxidization of diamond to give higher barrier height that results in low reverse leakage current [9,10], and the leakage current of diamond SBDs is observed as low as 10 (measurement limit) at 1.5 MV/cm, even at the high temperature (440K).…”
Section: Sbd Devicementioning
confidence: 75%
“…However, the experimentally observed breakdown of diamond-based diodes was 1-3 MV cm À1 [1,2], suggesting that numerous extrinsic factors lower the breakdown voltage. Crystalline defects of diamond are the most probable cause of increasing the leakage current and inducing the electric field breakdown.…”
Section: Introductionmentioning
confidence: 97%